MANAJEMEN KOMUNIKASI PEKERJA ASING DI INDONESIA DALAM PERSPEKTIF MATOUSCHKANIAN MICHAEL KAYE - TABRANI SJAFRIZAL (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to reveal the communication management of foreign experts working in Indonesia in interactions with Indonesian local workers. Included in the study material in this study are local workers who work in foreign companies, where most of the workers are foreigners, so these local workers, even though they work in their own country, they will still experience a culture shock at the foreign company. With Michael Kaye's communication management theory approach, the research problem can be formulated, how the attitude of foreign experts in seeing Indonesia's local communication culture system influences the formation of self-concepts and communication competencies in interactions with local Indonesian workers. This study uses a qualitative method, with a phenomenological approach that seeks to uncover the meaning of communication management by foreign experts. By interviewing foreign expert informants from various countries. This study found that foreign experts carried out empathy, acculturation, ethnocentrism and Dynamics Stress-Adaptation-Growth. towards local culture, thus affecting interpersonal sensitivity. and social competence in interactions with local workers. Ekspertariat who work in Indonesia, especially Jakarta deal with differences in the work and circumstances around them make adjustments to empathize, acculturation, and reduce ethnocentrism of their culture. Adjustment steps can be described using the Kim model, namely Dynamics Stress-Adaptation-Growth. This process will proceed when challenged to face a new cultural environment.